2020
DOI: 10.1002/gcc.22913
|View full text |Cite
|
Sign up to set email alerts
|

DICER1‐associated embryonal rhabdomyosarcoma and adenosarcoma of the gynecologic tract: Pathology, molecular genetics, and indications for molecular testing

Abstract: Gynecologic sarcomas are uncommon neoplasms, the majority occurring in the uterus. Due to the diverse nature of these, the description of “new” morphological types and the rarity of some of them, pathological diagnosis and treatment is often challenging. Finding genetic alterations specific to, and frequently occurring, in a certain type can aid in the diagnosis. DICER1 is a highly conserved ribonuclease crucial in the biogenesis of microRNAs and mutations in DICER1 (either somatic or germline) have been detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 115 publications
3
58
0
Order By: Relevance
“…Despite a similar or in some instances even identical morphology, the presence of cartilaginous nodules has previously been described in DICER1-associated ERMS, a finding that is confirmed by the current study [7,20]. Similarly, we report osteoid formation in conjunction with DICER1 mutations in a uterine ERMS, which has previously been reported in two cases of DICER1-associated ERMS of the female genital tract [34,40]. Thus, identification of cartilaginous nodules and/or osteoid formation in ERMS of the genitourinary tract, including the uterus, may suggest a DICER1-association.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Despite a similar or in some instances even identical morphology, the presence of cartilaginous nodules has previously been described in DICER1-associated ERMS, a finding that is confirmed by the current study [7,20]. Similarly, we report osteoid formation in conjunction with DICER1 mutations in a uterine ERMS, which has previously been reported in two cases of DICER1-associated ERMS of the female genital tract [34,40]. Thus, identification of cartilaginous nodules and/or osteoid formation in ERMS of the genitourinary tract, including the uterus, may suggest a DICER1-association.…”
Section: Discussionsupporting
confidence: 91%
“…These results are in line with a recent report by de Kock et al who reported a series of 19 DICER1-associated uterine ERMS with a median age at diagnosis of 30 years [7]. In contrast, a younger median age of 16 years at diagnosis of patients with DICER1associated ERMS arising anywhere in the female genital tract was published in a recent meta-analysis [34]. Our results suggest that on the other hand most extrauterine ERMS, more specifically DICER1-wt ERMS, usually do not occur in older patients [5].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There have been studies that suggest that the DICER1 mutation which causes dysregulation of miRNA and activates oncogenes may play a part in this process [8,17,18]. A hypothesis has been formed, stating that the DICER-1 mutation is present in ERMS developing in tissues derived from Mulerrian ducts, i.e., the uterus, cervix, upper part of the vagina and the fallopian tubes [19]. Moreover, a study of 17 cases has proved that DICER-1 mutation occurs more often in older patients, while in younger ones, ERMS usually develops with no connection to that mutation.…”
Section: Discussionmentioning
confidence: 99%
“…While Apellaniz-Ruiz in their review showed that nearly all gynecologic ERMSs (except vaginal tumours) were DICER1 -associated, Doros et al detected DICER1 mutation in only 3.8% (2/52) cases of sporadic ERMS and the Children's oncology group cohort of pediatric rhabdomyosarcomas showedDICER1 germline mutation in 4.4%. 10,[17][18][19][20] DICER1 -associated central nervous system sarcomas also have a high association with rhabdomyosarcomatous differentiation. 8,21,22 Our CNS case mimicked mesenchymal chondrosarcoma, though it expressed ERMS markers.…”
Section: Discussionmentioning
confidence: 99%